2014
DOI: 10.12691/jfnr-2-8-12
|View full text |Cite
|
Sign up to set email alerts
|

Cheddar Cheese from Cow Milk with Elevated Conjugated Linoleic Acid Levels

Abstract: The aim of the study was to evaluate the effect of feed management on conjugated linoleic acid (CLA) level in milk and subsequently on fatty acid profile of cheese. Twenty cows were divided into 2 groups, fed on grass silage and pasture feed with sunflower supplementation for 14 days. Milk samples were collected and analyzed for composition and fatty acid profile using gas chromatograph. Cheddar cheese was manufactured from both milk types and ripened for 120 days. During ripening, it was analyzed for composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…13.61%. The buffalo milk has higher content of total solids, lactose, fat and protein than cow milk, which makes it suitable for manufacturing of milk products, especially cheese production (Rafiq et al, 2016;Murtaza et al, 2014). Results of these current analyses were agreed with the findings of protein, fat, acidity and pH of buffalo milk by Ahmad et al (2013).…”
Section: Resultssupporting
confidence: 85%
“…13.61%. The buffalo milk has higher content of total solids, lactose, fat and protein than cow milk, which makes it suitable for manufacturing of milk products, especially cheese production (Rafiq et al, 2016;Murtaza et al, 2014). Results of these current analyses were agreed with the findings of protein, fat, acidity and pH of buffalo milk by Ahmad et al (2013).…”
Section: Resultssupporting
confidence: 85%
“…The results of some studies indicate that e.g. the industrial technological processing, the time of ripening, or the applied additions may promote an increase of CLA participation in fatty acids composition of some types of cheeses (Bzducha--Wróbel and Obiedziński, 2009;Kim et al, 2009;Lin, 2000;Murtaza et al, 2014). The carried out studies proved that the CLA contents in the examined commercial and farmer cheeses showed no meaningful differences (Table 2).…”
Section: Commercial Cheesesmentioning
confidence: 96%
“…The proportion of CLA in milk from the pasture feeding season is four-fold higher than that from the cowshed feeding (Lipiński et al, 2012;Żegarska et al, 2006). The level of cis9trans11 C18:2 acid in dairy products may differ from the one in milk, being the raw material for their production (Lin, 2000;Murtaza et al, 2014). The results of some studies indicate that e.g.…”
Section: Commercial Cheesesmentioning
confidence: 99%
“…Its content in milk fat ranges from 2.3 to 6.0 mg/g of fat [ 77 , 78 ] and may be affected by many factors such as the animal feeding regime, breed, and age, as well as the lactation period [ 79 , 80 , 81 , 82 , 83 , 84 ]. The content of CLA in dairy products (cheeses and fermented drinks) is influenced by the conditions of technological processes, the additives used, the activity of the starter cultures added, and the ripening time [ 85 , 86 , 87 ].…”
Section: Resultsmentioning
confidence: 99%